SOSIALISASI DAN PELATIHAN PEMBUATAN PANGAN DARURAT COOKIES MOCAF PADA PRNA DESA DORANG - Sari, Fariza Yulia Kartika; Septiani, Septiani; Suwarto, Tri (Universitas Mataram, 2024)
Dorang Village is one of Jepara Regency's villages that frequently experiences flood disasters.The problem that often occurs there is the limited availability of ready-to-eat emergency food that is healthy and nutritious. This causes high morbidity and mortality rates in the community. PRNA (Nasyiatul Aisyiyah Branch Leader) is a partner from the women's study group. PRNA plays an active role in every food organization in public kitchens, which is coordinated by the Muhammadiyah Disaster Management Center (MDMC) and the Regional Disaster Management Agency (BPBD). The aim of this activity is to train partners in making emergency food that is healthy and nutritious and is expected to be useful as an initial step in responding to flood disasters in Dorang Village. This service activity method uses service-based learning which includes pre-service learning. Socialization and training on making emergency food and evaluation. The target of this activity is the 35 members of PRNA Dorang. The results of community service activities show that this activity is able to increase partners' knowledge regarding emergency food, examples of emergency food and emergency food requirements. Partners were also able to create emergency food innovation, namely mocaf cookies, as a first step in responding to the flood disaster in Dorang Village. Therefore, this community service activity has a real impact on partners directly and can support Dorang Village to become a disaster resilient village.